Investigation of enhanced adhesion of HEK293T cells on SAM-modified ITO surfaces using NMR metabolomics - Ochima, Oluseyi V.; Alonge, Oreoluwa; Pollak, Julie P.; Wang, Bo; Kuila, Debasish (Frontiers in Bioengineering and Biotechnology, 2025)
Organoids are self-organizing, three-dimensional structures that replicate the main features of an organ. It is a fast-evolving area of research in regenerative medicine and cell biology. While the primary or stem cells are adapted for most of the organoid systems, Human Embryonic Kidney (HEK) 293T cells have been used in specialized applications within organoid systems when genetic manipulation is necessary. Unfortunately, HEK293T cells often suffer from loose adherence, which limits their applications in organoid formation. To improve cellular adhesion and proliferation, and to provide insights into the pathways involved in adhesion, HEK293T cells were cultured on a glass substrate sputtered with indium tin oxide (ITO) that is covered with a self-assembled monolayer (SAM) of 3-(mercaptopropyl) trimethoxysilane (MPS) (hereafter known as ITO-MPS SAM-coated substrate), a SAM of 3-(aminopropyl) triethoxysilane (APTES), and a SAM of 1-octadecanethiol (ODT). The ITO-MPS SAM scaffold yielded the most promising results, based on cell proliferation using MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide) assays. Nuclear Magnetic Resonance (NMR) spectroscopy was used to analyze the metabolomics present in the media with and without ITO-MPS-SAM coated substrates for a period of 120 h. The findings from the MTT assays demonstrate improved cell adhesion and proliferation on the ITO-MPS SAM-scaffold. The confocal microscopy images are consistent with these findings and provide a visual confirmation of the enhanced cellular environment. The metabolomic analysis yielded twenty-six metabolites, including sixteen adhesion promoters and modulators. These findings provide valuable insights into optimizing substrate conditions for improving cell adhesion and proliferation in HEK293T cells, potentially enhancing 3D cell culture and organoid research. The study also highlights novel metabolomic changes associated with improved cellular adhesion, contributing to the broader field of regenerative medicine and tissue engineering.